Fintech returns - Covid-19 and economic policy uncertainty - Pham, Phat Tien; Nguyen, Thi Huyen My (Tạp chí Khoa học HUFLIT, 2022)
This study investigates the impact of COVID-19 on fintech return in the context of economic policy uncertainty. The findings show that no evidence of the difference between the return and abnormal return of the fintech stock in the period of COVID-19; the fintech return will be higher in the case of economic policy uncertainty increase; and the increase of the number of confirmed COVID-19 cases and deaths is negatively associated with fintech return. In contrast, the ratio of deaths on confirmed cases is optimistic concerning fintech return.